1994
DOI: 10.1021/bi00195a002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Inactivation of Prostaglandin Endoperoxide Synthases by N-(Carboxyalkyl)maleimides

Abstract: N-(Carboxyalkyl)maleimides were synthesized as potential inhibitors of prostaglandin endoperoxide synthase (PGHS). Inactivation of the cyclooxygenase and peroxidase activities of PGHS occurred in a biphasic manner with extremely rapid inactivation followed by slow, time-dependent inactivation. The carboxylic acid moiety was required for rapid inactivation. Optimal inhibition was observed with N-(carboxyheptyl)maleimide, which inhibited the cyclooxygenase activity of ovine PGHS-1 with an IC50 of 0.1 microM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…We have recently shown that maleimide derivatives tethered to a series of medium-length fatty acids exhibit much more potent cyclooxygenase inactivation. The most potent of these inhibitors, N -(carboxyheptyl)maleimide, inhibits enyzme activity within seconds after mixing with a stoichiometric amount of PGHS protein …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that maleimide derivatives tethered to a series of medium-length fatty acids exhibit much more potent cyclooxygenase inactivation. The most potent of these inhibitors, N -(carboxyheptyl)maleimide, inhibits enyzme activity within seconds after mixing with a stoichiometric amount of PGHS protein …”
Section: Introductionmentioning
confidence: 99%
“…The most potent of these inhibitors, N-(carboxyheptyl)maleimide, inhibits enyzme activity within seconds after mixing with a stoichiometric amount of PGHS protein. 13 The lack of PGHS inhibition by the N-(carboxyheptyl)succinimide suggests that this rapid inhibition results from covalent modification of the protein. Varying the length of the alkyl chain in N-(carboxyalkyl)maleimides alters their potency as rapid inhibitors but does not significantly affect their ability to inhibit the enzyme on prolonged incubation (∼30 min).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that the products were GSH-IP (Marnett et al, 1983), were used as a source of PGS. The peroxidase activity in the RSV microsomes was determined to be 5.4 mol/min/mg protein, using guaiacol as a substrate as described previously (Kalgutkar and Marnett, 1994). RSV microsomal incubations of 5-OHTBZ were fortified with reduced GSH (or GSH-IP) and initiated with either arachidonic acid or H 2 O 2 (to bypass the cyclooxygenase step of PGS).…”
Section: Formation Of Gsh Conjugate Of 5-ohtbz (M3) By Hrp Lc-ms/msmentioning
confidence: 99%
“…In recent years, aspirin was found to reduce the risk of heart attack and stroke. Aspirin is also suggested to be effective against colorectal cancer, although it has no effect on other types of cancers such as lung, breast, ovary, testis, lymphoma, and leukemia. The exact mechanism by which aspirin exerts its antitumor activity is not clear. However, NSAID drugs are found to block the synthesis of prostaglandins long chain fatty acid compounds that have various functions, including stimulation of cell proliferation and suppression of immune reaction, both of which are linked to tumor progression.…”
Section: Introductionmentioning
confidence: 99%